Laboratory Examination in Genital Chlamydia trachomatis Infection - Novianti Risky Reza; Tantari SHW (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Background: Chlamydia trachomatis (CT) is one of the most common agents caused nonspesific genital infections in both men and women worldwide and also in Indonesia. Chlamydial infection can be asymptomatic, became source of infection for the partner, and serious complication may be occurred. Early diagnosis and prompt treatment were needed to prevent the complication. Purpose: To review the advantages and disadvantages of numerous laboratory diagnostic methods of genital CT infections. Review: The gold standart in CT infection diagnosis was culture but it was difficult to do in clinical setting. Diagnosis by direct antigen methods for diagnosing CT infections, such as direct fluoresence assay (DFA),enzim immuno assay (EIA), nucleic acid detection, citology ,and serology can be done. Conclusion: Combining two or more different methods of laboratory examination  will give better results in diagnosis with better sensitivity and specificity.Key words: Chlamydia trachomatis, genital infection, laboratory.